REVITALISASI BAHASA ARAB DALAM KEHIDUPAN SOSIAL MASYARAKAT GORONTALO MELALUI PENDIDIKAN - Sarif, Suharia Ria; Hairuddin, Hairuddin; Kadir, Suleman D.; Samad, Musdelifa Abu; Bahri, Ratni Bt. Hj.; Hulantu, Nurfadila; Lauma, Siti Fatimah (Insan Cita : Jurnal Pengabdian Kepada Masyarakat, 2025)
The revitalisation of the Arabic language in Pone Village, Gorontalo, is very important given its role in the social and religious context of the community. Although Arabic is used in religious practices, the community's interest and ability in this language has decreased. One of the main causes is the lack of access to quality education and ineffective teaching methods. This article aims to improve the community's Arabic language skills through innovative educational approaches that are more interactive and contextualised. The methods used in this community service activity include a communicative approach that encourages active participation of participants, as well asintegration of local culture in learning. These activities include group discussions, recitations, and social activities that use Arabic as the medium of communication. The outcome of the programme is expected to improve participants' Arabic language skills and strengthen awareness of the importance of this language in their cultural identity. Evaluation at the end of the programme, through proficiency tests and feedback, will provide information on the effectiveness of the methods applied. By involving various levels of society, it is hoped that this programme can create an environment that supports the active use of Arabic, as well as strengthening cultural and social values in Pone village.